2020
DOI: 10.1007/s00122-020-03650-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterisation and linkage mapping of domestication syndrome traits in yellow lupin (Lupinus luteus L.)

Abstract: The transformation of wild plants into domesticated crops usually modifies a common set of characters referred to as ‘domestication syndrome’ traits such as the loss of pod shattering/seed dehiscence, loss of seed dormancy, reduced anti-nutritional compounds and changes in growth habit, phenology, flower and seed colour. Understanding the genetic control of domestication syndrome traits facilitates the efficient transfer of useful traits from wild progenitors into crops through crossing and selection. Domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The resistance to shattering provided by invulnerabilis is sufficient for the relatively humid climates of northern Europe but does not provide strong resistance in the comparatively arid climates of the Mediterranean or western Australia (Wolko et al, 2011). Recent studies suggest that a second pod shatteringrelated allele may exist in the yellow lupin population (Iqbal et al, 2020), although this allele has not yet been mapped or described in detail. Due to the incomplete resistance to pod shattering provided by invulnerabilis, the pyramiding of multiple shattering resistance alleles is required in L. luteus.…”
Section: Lupinus Sppmentioning
confidence: 99%
“…The resistance to shattering provided by invulnerabilis is sufficient for the relatively humid climates of northern Europe but does not provide strong resistance in the comparatively arid climates of the Mediterranean or western Australia (Wolko et al, 2011). Recent studies suggest that a second pod shatteringrelated allele may exist in the yellow lupin population (Iqbal et al, 2020), although this allele has not yet been mapped or described in detail. Due to the incomplete resistance to pod shattering provided by invulnerabilis, the pyramiding of multiple shattering resistance alleles is required in L. luteus.…”
Section: Lupinus Sppmentioning
confidence: 99%
“…The release of two white lupin high quality genome assemblies [ 27 , 28 ] provided an unprecedented opportunity to search for similar indels in FT homologs in this species, both by whole-genome shotgun and PCR-based approaches. Recent comparative mapping approach performed in yellow lupin, Lupinus luteus L., revealed that a major QTL for vernalization responsiveness in this species is localized in a linkage map segment syntenic to the narrow-leafed lupin genome region carrying the FTc1 gene [ 46 , 47 , 48 ]. All these observations support the conclusion on the highly conserved contribution of the FTc1 homologs into vernalization pathway in the Old World lupin clade.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of these traits include loss of pod shattering/seed dehiscence, loss of seed dormancy, reduced anti-nutritional compounds, changes in growth habit, phenology, flower colour, and seed colour. Understanding the genetic control of domestication syndrome traits facilitates the efficient transfer of useful traits from wild progenitors into crops through crossing and selection [ 205 , 207 ]. It has become apparent in recent years that understanding the nature of the plurality of processes underlying domestication syndrome is the key to understanding the origins of domestication.…”
Section: De Novo Domestication Of Wild Plantsmentioning
confidence: 99%
“…Despite all successes, gene editing approaches to the domestication of wild plants using domestication genes [ 11 , 202 , 207 ] should not be generally considered as simple one-time events in a single gene or generation. In contrast, de novo domestication literature and examples understand domestication as co-evolutionary interactions between plants and people that are complex, would require significant institutional and infrastructural investments, and can involve many disciplines.…”
Section: Reference Pan- and Super-pan Genome Sequences Provide A Strong Basis For The Location Of Domestication Syndrome Genesmentioning
confidence: 99%